Is Contrast-Enhanced Ultrasound Superior to Computed Tomography for Differential Diagnosis of Gallbladder Polyps? A Cross-Sectional Study - Yuan, Zhiqing; Liu, Xuesong; Li, Qiwei; Zhang, Yunhe; Zhao, Ling; Li, Fenghua; Chen, Tao (Frontiers in Oncology, 2021)
Objective To compare the clinical value of contrast-enhanced ultrasonography (CEUS) versus computed tomography (CT) for distinguishing neoplastic and non-neoplastic gallbladder polyps. Given whether laparoscopic cholecystectomy is needed, differential diagnosis of neoplastic and non-neoplastic gallbladder polyps is more important than benign and malignant polyps. Methods A total of 89 consecutive patients with polypoid lesions of the gallbladder > 10 mm in size without local invasion or distant metastasis during primary screening were enrolled in this prospective and comparative study. All patients who met the inclusion criteria underwent CEUS and CT examinations prior to surgical resection. The enhancement patterns and microvascular imaging types were analyzed on CEUS. The maximum diameter and CT value of the lesions were also recorded and subjected to a comparative analysis. The clinical value of the two diagnostic methods is compared. Results Of the 89 patients, there were 58 (65.2%) cases of non-neoplastic polyps and 31 (34.8%) cases of neoplastic polyps. The average diameter of neoplastic polyps was significantly higher than that of non-neoplastic polyps (P<0.001). The detection rate using CEUS was 100%. The proportion of perceived non-neoplastic polyps in the nonenhanced and arterial phases were 48.3% and 77.6%, respectively, which were significantly lower than those of neoplastic polyps (93.5%, P<0.001 and 100.0%, P<0.001, respectively). However, in the venous and delayed phases, all cholesterol polyps and neoplastic polyps were perceived. CT showed that non-neoplastic polyps exhibited delayed enhancement. On CEUS 29.0% neoplastic polyps showed a perfusion defect, whereas 6.9% non-neoplastic polyps showed a perfusion defect (P=0.005). The microvascular architecture of the lesions on CEUS was categorized into 4 types: spotty, linear, branched, and spinous, and there were significant differences between the two groups (P<0.001). The sensitivities and specificities were 87.10% and 68.97% for CEUS and 83.87% and 77.59% for CT, respectively (P=0.406). Conclusions CEUS and CT are useful for differential diagnosis of neoplastic and nonneoplastic polypoid lesions of the gallbladder. Diagnostic efficacy was comparable between CEUS and CT. Thus, CEUS is preferred over CT in the differential diagnosis of neoplastic and non-neoplastic gallbladder polyps due to its comparable diagnostic efficacy and lack of radiation dose.